Strategi Pemasaran dan Implementasinya dalam Lembaga Pendidikan - Khoirul Anam (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2013)
According to the perspective of marketing, Islamic education institution is categorized as a non profit organization. It is an activity to serve students and stakeholders. Since principally the function of the institution to serve, therefore, the marketing strategy is done by: identification of the market, segmenting and positioning of the market, differentiating product, and marketing communication. Through implementing those strategies, an educational institution can compete with others. In other words, by implementing certain strategies, an educational institution can win the competition, especially in improving the number of students from year to year.